Rana – tożsamość – podmiot: Zmagania kultury i literatury ukraińskiej z traumą postkomunistyczną. Od postkolonialności do dekolonialności (zarys projektu badawczego) .......... 115 - Matusiak, Agnieszka (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
WOUND – IDENTITY – SUBJECT: THE STRUGGLES OF UKRAINIAN CULTURE AND LITERATURE WITH POST-COMMUNIST TRAUMA. FROM THE POST-COLONIAL TO THE DECOLONIAL (OUTLINE OF A RESEARCH PROJECT)This text is a presentation of a research project aimed at developing the affective history of Ukrainian literature at the end of the 20th and 21st centuries. The author’s key research tool is post-communist trauma (with particular emphasis on posttraumatic growth) embedded in generational optics. According to the author of the project, these are key categories for the analysis and description of the process of shaping the cultural identity of the Ukrainian society of the era of systemic transformation after the collapse of the Soviet Union, of which process literature was / is a sensitive recorder. The author adopts decolonial thinking as the methodological horizon.